The Synthesis and Physical Properties of Magnesium Borate Mineral of Admontite Synthesized from Sodium Borates - Azmi Seyhun Kipcak; Meral Yildirim; Sureyya Aydin Yuksel; Emek Moroydor Derun; Sabriye Piskin (Advances in Materials Science and Engineering)
Magnesium borates are significant compounds due to their advanced mechanical and thermal durability properties. This group of minerals can be used in ceramic industry, in detergent industry, and as neutron shielding material, phosphor of thermoluminescence by dint of their extraordinary specialties. In the present study, the synthesis of magnesium borate via hydrothermal method from sodium borates and physical properties of synthesized magnesium borate minerals were investigated. The characterization of the products was carried out by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) and Raman spectroscopies, and differential thermal analysis and thermal gravimetry (DTA/TG). The surface morphology was examined by scanning electron microscopy (SEM). B2O3 content was determined through titration. The electrical resistivity/conductivity properties of products were measured by Picoammeter Voltage Source. UV-vis spectrometer was used to investigate optical absorption characteristics of synthesized minerals in the range 200–1000 nm at room temperature. XRD results identified the synthesized borate minerals as admontite [MgO(B2O3)3·7(H2O)] with code number “01-076-0540” and mcallisterite [Mg2(B6O7(OH)6)2·9(H2O)] with code number “01-070-1902.” The FT-IR and Raman spectra of the obtained samples were similar with characteristic magnesium borate bands. The investigation of the SEM images remarked that both nano- and microscale minerals were produced. The reaction yields were between 75.1 and 98.7%.